The Effect of Clustering Technique to Students’ Writing Ability in MA Pi DDI Mangkoso Barru - Azizah Jamal Passolowongi; Nurdin Noni; Samtidar Samtidar (Journal of Excellence in English Language Education, 2022)
The goal of the objectives of this article was to see how far some of the clustering can improve students' writing skills. In this work, a quasi-experimental approach was adopted. the method with a sample size of 40 people, 20 from 20 participants in the experimental group from the control group. The research came to the conclusion that students a part of the experimental group who were taught using the clustering method were better than the control sample of students who were taught the conventional way. This is evidenced by the as an alternative (Ho) is accepted, while the absence of a hypothesis (HI) is rejected after applying the post-test when higher than or equal to the t-table value, the test is t-tested formula is used. The meaning of the application of grouping has a significant impact on students' writing skills at MA Pi DDI Mangkoso.